Colombia : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2022)
The pandemic led to Colombia's largest recession on record, but the economy bounced back strongly in 2021. The banking system has so far weathered the shock well, with the help of a strong policy and support response and strong initial position. Colombia is exposed to elevated external financing risks and the further prolongation of the pandemic. Large and complex financial conglomerates with increasing cross-border exposures dominate the financial system. The consumer-credit portfolio deserves attention as it has been growing fast and had high impairment rate during the pandemic.